EFEKTIFITAS PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION (AIR) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Hasibuan, Siti Annisah; Nasution, Febriani Hastini; Siregar, Lukman Hakim (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2021)
The aim of this study is to describe the effectiveness of using AIR learning on students’ critical thinking ability at the eleventh grade students of SMA Swasta Abdi Utama Sibuhuan. This research was conducted by applying experimental (one group pre test post test design) with 28 students as the sample and they were taken by using total sampling technique. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using AIR learning was 3.2 (very good category) and (b) the average of on students’ critical thinking ability before using AIR learning was 47.19 ( fair category) and after using AIR learning was 84.24 ( very good category).Furthermore, by using pair sample ttest and help SPSS version 22, the result showed the significant value was less than 0.05 (0.000<0.05). It means, air learning was effective used on students’ critical thinking ability at the eleventh grade students of SMA Swasta Abdi Utama Sibuhuan.